Кубанська музична фольклористика: етапи становлення - Супрун-Яремко, Н. (Народна творчість та етнографія, 2007)
On the basis of materials related to the history of the Ukrainians in Kuban (of 1792) the author determines that priests, historians, ethnographers, students of local lore, regents, choirmasters, teachers and poets were at the beginnings of Kuban musical study of folklore. The formation of Kuban musical folklore had 3 stages: concert and representational stage (of 1818), stage of collection (of 1865), transcriptional and publishing stage. Bihday, Kontsevych, Zakharchenko and Koshyts made the most considerable contribution in development of this science. The author of the article gives detailed information about their biographies.